Kajian Kebutuhan Pengembangan Rumah Sakit Pemerintah Daerah Kelas B di Provinsi Sulawesi Utara - Oktamianti, Puput (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2019)
The existence of regulations regarding regional referrals established by the central government, encourages the North Sulawesi regional government to provide regional referral hospitals that have service capabilities as class B hospitals. For the development of North Sulawesi Provincial Hospital in the future, basic information on services, facilities, facilities and infrastructure, as well as market coverage that depends on system governance, HR capabilities, physical buildings and equipment and resources. The purpose of this study is to examine the service needs of North Sulawesi Provincial Hospital which includes demographic studies, socio-economic studies, studies of morbidity and mortality, study of policies and regulations, environmental studies and studies of land, building and resource needs. The primary data collection method was carried out through in-depth interviews and land measurements and document review on North Sulawesi Province health report documents, 2013 Riskesdas Report, Sulawesi Dalam Angka, staffing data and health equipment and equipment data. The results of the study indicate that the construction of the North Sulawesi provincial hospital as a provincial referral hospital with hospitals equivalent to class B and 400 TT is feasible. Excellent services that can be developed include the Integrated Stroke Service Center and the services of the heart and blood vessels. To fulfill the development of the RSUD, it is necessary to have a strategy to fulfill health human resources and various health facilities to support the implementation of the RSUD as a class B hospital.